1992
DOI: 10.1111/j.1365-2249.1992.tb03074.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo levels and in vitro production of interferon-gamma in fibrosing interstitial lung diseases

Abstract: SUMMARY The in vivo role of interferons in the development of fibrosis is not fully understood but it is known that interferons can suppress fibroblast proliferation and collagen synthesis in vitro. We have recently demonstrated that in a group of patients with sarcoidosis having predominant pulmonary involvement, patients with the highest levels of circulating interferon‐gamma (IFN‐y) more frequently resolved on corticosteroids, suggesting that they had a less‘fibrotic’ component to their disease. We now repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(32 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Previous findings have indicated that IFNg inhibits fibroblast proliferation in pulmonary tissue, thereby reducing extracellular matrix and connective tissue formation (Li & Zhai, 2008). These findings have been corroborated by observations on the complete or partial deficiency of IFNg in patients with pulmonary fibrosis compared to normal subjects (Gurujeyalakshmi & Giri, 1995;Prior & Haslam, 1992). Besides, IFNg can counterbalance T H 2-associated cytokine overproduction and down-regulate gene expression of TGFb-one of the most potent fibrogenic factors (Du Bois, 1999;Ziesche & Block, 2000).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous findings have indicated that IFNg inhibits fibroblast proliferation in pulmonary tissue, thereby reducing extracellular matrix and connective tissue formation (Li & Zhai, 2008). These findings have been corroborated by observations on the complete or partial deficiency of IFNg in patients with pulmonary fibrosis compared to normal subjects (Gurujeyalakshmi & Giri, 1995;Prior & Haslam, 1992). Besides, IFNg can counterbalance T H 2-associated cytokine overproduction and down-regulate gene expression of TGFb-one of the most potent fibrogenic factors (Du Bois, 1999;Ziesche & Block, 2000).…”
Section: Introductionsupporting
confidence: 63%
“…Several lines of evidence have shown that T H 2 cytokines and fibroblast count are elevated in patients with pulmonary fibrosis, which enhance TGFb status and accumulation of collagen in the airways (Raghu et al, 1989;Rahman, 2005). There is also evidence indicating impaired IFNg production in patients with fibrosing lung diseases (Prior & Haslam, 1992) that results in the over-proliferation of fibroblasts and excessive collagen production.…”
Section: Discussionmentioning
confidence: 99%
“…[2007] study, IPF lymphocytes showed higher than normal production of IL-4 but not of IFN-γ . Although this data need to be considered with caution since the diagnosis of CFA might include subjects with NSIP in addition to IPF/UIP patients, it is worth noticing that in Prior and Haslam's [1992] study, higher IFN-γ levels were associated with better response to corticosteroid treatment and better prognosis in CFA-affected individuals.…”
Section: Exaggerated Immunity and Inflammationmentioning
confidence: 91%
“…In a "cryptogenetic fibrosing alveolitis" (CFA) (a synonym of IPF) study, Prior and Haslam [1992] found that most diseased subjects had low levels of circulating IFN-γ . Wallace and Co-workers showed that most lymphocytes infiltrating the interstitium in CFA expressed IL-4 and IL-5 but almost none IFN-γ [Wallace et al 1995]; type II alveolar epithelial cells expressed IL-4, but no IFN-γ at sites of disease, while they expressed both IL-4 and IFN-γ in allergic alveolitis [Wallace and Howie 1999], suggesting that the TH2 type response may be important in the pathogenesis of lung fibrosis.…”
Section: Exaggerated Immunity and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation